Analysis of Gold Mining Company Stock Proses on the IDX Based on the Roles of Profitability, Earnings Per Share, and Global Gold Price Fluctuation - Alya Juanita; Fanlia Prima Jaya; Arfie Yasrie (PT. Hanken Sukses Jaya, 2026)
This study aims to analyze the effect of Return on Investment (ROI) and Earning Per Share (EPS) on stock prices through world gold prices as an intervening variable in gold mining sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2025 period. This research employed a quantitative approach using secondary data obtained from annual financial reports and world gold price data. The sample consisted of five gold mining companies selected through purposive sampling. Data were analyzed using descriptive statistics, classical assumption tests, and regression analysis with an intervening variable. The results indicate that ROI and EPS do not significantly affect world gold prices. However, ROI and EPS have a positive and significant effect on stock prices. Furthermore, world gold prices are able to mediate the relationship between ROI, EPS, and stock prices. The study concludes that profitability indicators and world gold prices are important factors influencing stock prices in the gold mining sector